Ghosts of Thanksgiving Past, Present, and Future - Rah, Soong-Chan (The review of faith & international affairs, 2021)
The Thanksgiving story contributes to the formation of the American social imagination. The social imagination of Thanksgiving emerges from the larger context of the American mythology, specifically drawing from the self-perception of exceptionalism and triumphalism. These imaginaries are shaped by internalized narratives such as the Doctrine of Discovery. The Thanksgiving story as it continues to be re-enacted, affirms the assumption of an exceptional people, chosen by God to bring hope and life into the New World. How does one begin to theologically deconstruct this mythology and begin to construct a more helpful imagination around the Thanksgiving narrative?